Diagnóstico de fibrosarcoma felino por imagen termográfica - Sanz Tolón, A.; Vicente Pubiano, M.; Barneto Carmona, A.; Sánchez- Vizcaíno Rodríguez, J.M. (Revista Complutense de Ciencias Veterinarias, 2008)
Thermography is a complentary diagnosis method which is based on the reception of infrared radiations that bodies emit and reflex, that are proportional to surface temperature. Using a thermographic camera these radiations are turned into digital images which can be understood according to a colour scale. Through thermographic images, thermal changes that affect dermis and epidermis can be located, and they can also be delimitated with precision. This method permit to make an easy diagnosis of any pathology related with thermal changes. This technique has been used to study two clinical cases in order to prove the potential of the method as complementary diagnosis on feline skin tumor such as fibrosarcoma.
Keywords: Thermography; Diagnosis; Tumor